The Effectiveness of Banyuwangi Local Regulation Number 7 Year 2017 On The Supervision Of Madrasah Diniyah Takmiliyah - Silvia Maulida (Al-Balad: Journal of Constitutional Law, 2019)
The implementation of Banyuwangi District Regulation Number 7 Year 2017 regarding Compulsory Education for Madrasah Diniyah Takmiliyah has not been effective. The formulation of the problem chosen is How Effective is the supervision of Madrasah Diniyah Takmiliyah according to Regional Regulation of Banyuwangi District Number 7 of 2017 concerning Compulsory Education for Madrasah Diniyah Takmiliyah? What are the supporting and inhibiting factors of Regional Regulation Supervision of Banyuwangi District Number 7 of 2017 concerning Compulsory Education for Madrasah Diniyah Takmiliyah? This research is an empirical legal research using a sociology and legislation approach that describes in depth about the object under study. And data collection methods used are interviews as primary data and literature as secondary data. The analysis technique uses descriptive-analitive. The results showed that Supervision of Madrasah Diniyah was not yet effective. Researchers found that only 20% of the areas in Banyuwangi have received information since the regulation was enacted. In addition to the coverage, interviews revealed that socialization was still limited to village officials and did not reach Madrasah diniyah educators or the community. The local government does not oversee this program and there is no continuity between institutions related to the Madrasah Diniyah compulsory education program. Supervision of Madrasah Diniyah Takmiliyah is ineffective, government attention and content in the supervision function are still low, the role of government is considered to be very lacking. From previous data, such as from the effectiveness factors of the law as well as supporting and inhibiting factors that have been analyzed